Oncological outcome of conversion surgery after preoperative chemotherapy for metastatic pancreatic cancer - Hank, Thomas; Klaiber, Ulla; Hinz, Ulf; Schütte, Denise; Leonhardt, Carl-Stephan; Bergmann, Frank; Hackert, Thilo; Jäger, Dirk; Büchler, Markus W.; Strobel, Oliver (Annals of surgery, 2023)
Objective: - To investigate the outcome of conversion surgery in patients with metastatic pancreatic cancer (mPDAC) and to identify patients who may benefit from this approach. - Background: - The role of conversion surgery in patients with mPDAC and exceptional response to chemotherapy remains unclear. - Methods: - Patients who underwent surgical exploration for mPDAC following chemotherapy between 2006 and 2019 were included. Data on demographics, oncologic treatment, pathology, and postoperative outcomes were analyzed. Univariate and multivariate survival analyses were performed. - Results: - Some 173 patients received preoperative chemotherapy and underwent surgical exploration. Ninety-three patients underwent resection of the primary tumor and metastatic sites, 80 patients underwent exploration only. In the resection subgroup, 45 patients had complete pathological response of metastases (ypM0) and 48 patients had residual metastases (ypM1). ypM0 status was associated with lower carcinoembryonic antigen levels and lower ypN stage. Overall survival after resection was 25.5 months in ypM0, 10.7 months in ypM1, and 8.1 months in patients without resection (P<0.001). Additional adjuvant chemotherapy was significantly associated with prolonged survival in resected patients (29.0 vs 14.8 mo, P=0.024) as well as in ypM0 (29.1 vs 19.2 mo, P=0.047). Multivariable analysis identified conversion surgery, carbohydrate antigen 19-9 (CA19-9) and time of resection as independent prognostic markers for the entire cohort. CA19-9, ypM0 and adjuvant treatment were independent predictors of survival in the resection subgroup. - Conclusion: - In patients with mPDAC and ypM0 status after chemotherapy, surgical resection is associated with encouraging survival. mPDAC patients with exceptional response to chemotherapy may be candidates for exploration and for resection in ypM0. Adjuvant chemotherapy may provide an additional survival advantage.
Gesehen am 21.07.2023